Antecedent Factor on Career Success - Diana Titik Widayati; Sandra Irawati (Journal of Career and Entrepreneurship, 2023)
The purpose of this research is to determine and analyze the influence of self-motivation, self-efficacy, and career planning on career success. This research was conducted by FEB alumni who had completed a tracer study and provided testimonials while studying at FEB UMM. The sample was taken from 5% of the 2300 population, namely 165. The technique for determining the sample was to distribute questionnaires via Google Forms to all respondents contacted via WA and Cloud. After 165 questionnaires were filled, the data collection process was stopped. The analytical tool used is multiple regression with SPSS. The research results show that self-motivation has no effect on career success, while self-efficacy and career planning have a positive effect on career success.